Surface characteristics of dentin experimentally exposed to hydrofluoric acid - Pioch, Thomas; Jakob, Heiko; García‐Godoy, Franklin; Götz, Hermann; Dörfer, Christof; Staehle, Hans Jörg (European journal of oral sciences, 2003)
The purpose of this study was to test the effect of hydrofluoric acid (HF) on the surface characteristics of dentin in vitro. Dentin was exposed in 50 human molars and divided into five groups according to different etching schedules: (i) no etching, (ii) 15 s HF, (iii) 15 s H3PO4, (iv) 15 s HF and 15 s H3PO4, (v) 15 s H3PO4 and 15 s HF. Teeth were examined under a scanning electron microscope equipped with energy-dispersive X-ray (EDX) or two layers of fluorescence-labeled primer followed by the composite were applied, and the teeth were sectioned and examined using confocal laser scanning microscopy (CLSM). With scanning electron microscopy, no openings of dentinal tubules were found in groups (i), (ii), and (iv). In group (v) only a few tubules were opened and in group (iii) the smear layer was completely removed and tubules appeared open. The EDX analysis revealed that fluoride was incorporated into the dentin surface when HF was used. With CLSM, distinct hybrid layers could be detected only in group (iii). In group (v) the hybrid layer appeared less established compared with group (iii). No dentin hybridization was found in groups (i), (ii), and (iv). It is concluded that HF has the ability to close the openings of dentin tubules which were opened due to etching by phosphoric acid and cannot dissolve the smear layer.
Gesehen am 19.02.2021